The effect of phonons-surface and grain-boundary scattering on electrical properties of metallic Ag - Fairooz A. Meteab; Mohammed, May A. S.; Ulvi Kanbur (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Explain in this study, thickness has an inverse relationship with electrical resistivity and a linear relationship with Grain boundary scattering. According to the (Fuchs-Sondheier, Mayadas-Shatzkces) model, grain boundary scattering leads To an Increase in electrical Resistivity. The surface scattering Coefficient of Ag, which Fuchs-Sondheier and Mayadas-Shatzkces measured at , Ag’s grain boundary reflection coefficient , which Mayadas-Shatzkces measured at , If the concentration of material has an effect on metal’s electrical properties, According to this silver is a good electrical conductor and is used frequently in electrical and electronic circuits.